THE INFLUENCE OF WORK FACILITIES ON IMPROVING EMPLOYEE PERFORMANCE AT PPKS (PALM PALM RESEARCH CENTER) MEDAN: PENGARUH FASILITAS KERJA TERHADAP PENINGKATAN KINERJA KARYAWAN PADA PPKS (PUSAT PENELITIAN KELAPA SAWIT) MEDAN - Misbahhuddin (LPPM UPMI, 2023)
This study aims to determine the effect of Work Facilities, Work Discipline and Compensation on Improving Employee Performance with Motivation as an Intervening Variable at PPKS (Palm Oil Research Center) Medan. This research is quantitative research with a population of 365 people and a sample of 35 employees. The sample technique used is simple random sampling, the main method used is distributing questionnaires, while the auxiliary method used is documentation testing the research hypothesis using multiple linear analysis, partial t test. X1) on Increasing Employee Performance (Y) for PPKS Medan employees. This test proves that partially (t) Work Facilities do not have a significant effect on increasing employee performance.